Shifting brain circuits in pain chronicity. Issue 15 (12th July 2019) - Youssef, Andrew M.; Azqueta‐Gavaldon, Monica; Silva, Katie E.; Barakat, Nadia; Lopez, Natalia; Mahmud, Farah; Lebel, Alyssa; Sethna, Navil F.; Zurakowski, David; Simons, Laura E.; Kraft, Eduard; Borsook, David
Abstract: The evaluation of brain changes to a specific pain condition in pediatric and adult patients allows for insights into potential mechanisms of pain chronicity and possibly long‐term brain changes. Here we focused on the primary somatosensory system (SS) involved in pain processing, namely the ventroposterolateral thalamus (VPL) and the primary somatosensory cortex (SI). We evaluated, using MRI, three specific processes: (a) somatotopy of changes in the SS for different pain origins (viz., foot vs. arm); (b) differences in acute (ankle sprain versus complex regional pain syndrome‐CRPS); and (c) differences of the effects of CRPS on SS in pediatric versus adult patients. In all cases, age‐ and sex‐matched individuals were used as controls. Our results suggest a shift in concurrent gray matter density (GMD) and resting functional connectivity strengths (rFC) across pediatric and adult CRPS with (a) differential patterns of GMD (VPL) and rFC (SI) on SS in pediatric vs. adult patterns that are consistent with upper and lower limb somatotopical organization; and (b) widespread GMD alterations in pediatric CRPS from sensory, emotional and descending modulatory processes to more confined sensory‐emotional changes in adult CRPS and rFC patterns from sensory‐sensory alterations in pediatric populations to a sensory‐emotional change in adult populations. These results support the idea that pediatric and adult CRPS are differentially represented and may reflect underlying differences in pain chronification across age groups that may contribute to the well‐known differences between child and adult pain vulnerability and resilience.